'Invasion debt' after extensive land-use change: An example from eastern Australia. (15th January 2022) - Lebbink, Gabrielle; Dwyer, John M.; Fensham, Roderick J.
Abstract: Land-use change, and associated land clearing/conversion and fragmentation are major drivers of biodiversity decline across the globe. The spread of invasive species is a well-recognised consequence of land-use change. The extent and intensity of invasion however is often difficult to assess due to a lack of temporal data. Using detailed mapping information for 130, 950 km 2 of sub-coastal Queensland, Australia and results from field surveys we investigated changes to land-use, the extent of remnant (intact) vegetation and the spread of prominent invasive plant species over time (1997–2018). In the 50 years prior to 1997 the area underwent significant land development (mostly for livestock grazing and crops), resulting in a reduction of 45% of its remnant vegetation. Despite key policy developments aimed at protecting the remaining vegetation and species, 7392 km 2 was cleared/converted between 1997 and 2017, mainly for the expansion of grazing and cropping lands. Vegetation types specifically listed for national protection under these policies were some of the greatest affected, highlighting the need for improved implementation and regulation of these control measures. Within remaining fragments of remnant vegetation, the cover and presence of two invasive perennial grass species indian couch ( Bothriochloa pertusa) and buffel grass ( Cenchrus ciliaris ) increased significantly during this time period. There was also a moderate increase in the cover and presence of the annual herb Parthenium weed ( Parthenium hysterophorus ). The spread of these species within the landscape likely reflects an 'invasion debt', incurred from an intense history of land-use within the region and we predict this trend will continue to threaten remnant ecosystems. Highlights: Grazing and cropping industries driving habitat loss and fragmentation. Policy failing to protect threatened species and ecosystems. 'Invasion debt' incurred from intense historical land use.